Wave diffraction on gimbal - Гнатейко, Нонна Валентиновна (Eastern-European Journal of Enterprise Technologies, 2010)
The problem of linearly-resilient interaction of gimbal is decided as two coaxial cylinders with external wave influence. Nature of origin moving of surface is analytically explained because of diffraction effects.